Portugal : Second Post-Program Monitoring. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of the Second Post-Program Monitoring Discussions with Portugal. Portugal's economic recovery remains on track in 2015, boosted by rising exports and consumption, together with a recent upturn in investment. Real GDP expanded by 1.5 percent (year-over-year) in the first quarter, and is projected to increase 1.6 percent for the full year. A more forceful approach to corporate debt work-outs is needed to accelerate the structural transformation of the economy. The authorities should be proactive in putting in place a coordinated approach to debt work-outs to restructure the debts of viable firms, and move forward with liquidation of those that are no longer viable.